2014
DOI: 10.4161/bioe.28720
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological production of value-added carotenoids from microalgae

Abstract: We recently evaluated the relationship between abiotic environmental stresses and lutein biosynthesis in the green microalga Dunaliella salina and suggested a rational design of stress-driven adaptive evolution experiments for carotenoids production in microalgae. Here, we summarize our recent findings regarding the biotechnological production of carotenoids from microalgae and outline emerging technology in this field. Carotenoid metabolic pathways are characterized in several representative algal species as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 31 publications
1
41
0
2
Order By: Relevance
“…Nutritional supply, D. salina, may be used as an alternative to hormonal treatments to enhance reproductive performance. D. salina has high levels of beta-carotene, glycerol, protein and other fine chemicals (Gouveia et al, 2008;Ghasemi et al, 2011;Wichuk et al, 2014;Cuellar-Bermudez et al, 2015;Gong and Bassi, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutritional supply, D. salina, may be used as an alternative to hormonal treatments to enhance reproductive performance. D. salina has high levels of beta-carotene, glycerol, protein and other fine chemicals (Gouveia et al, 2008;Ghasemi et al, 2011;Wichuk et al, 2014;Cuellar-Bermudez et al, 2015;Gong and Bassi, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…D. salina has high levels of beta-carotene, glycerol, protein and other fine chemicals (Gouveia et al, 2008;Ghasemi et al, 2011;Wichuk et al, 2014;Cuellar-Bermudez et al, 2015;Gong and Bassi;, which might improve the quality of oocyte and support further embryonic development. Conclusion of our work (Senosy et al, 2017) indicated that D. salina supplemented to Boer goats (10 g/day/head) accelerated ovarian follicle development and significantly, increased follicle numbers (small, medium and large follicles).The improvement of oocyte quality in D. salina group compared to control one might be related to high levels of beta-carotene and elevation of plasma metabolites and hormones levels.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest β‐carotene content has been recorded in the halotolerant algae, Dunaliella bardawil (Chlorophyceae), which produced about 80 mg g −1 cell originally but the biomass content was not improved . Except for D. bardawil , the cellular content of β‐carotene in recombinant C. zofingiensis and Saccharomyces cerevisiae cells was less than 6 mg g −1 cell, and higher quantities are needed to simplify the downstream processing and improve the economics of the production processes. The production of β‐carotene with recombinant S. cerevisiae was not achieved by overexpressing PSY because carotene production in yeasts is through crt cluster genes (instead of psy gene) in carotenogenic pathway .…”
Section: Introductionmentioning
confidence: 99%
“…Mutagenesis, adaptive laboratory evolution (or ALE), and genetic engineering have been established as strategies for developing algal cell factories. Furthermore, systems biology and synthetic biology perspectives and approaches are emerging in the production of bioactive compounds, such as carotenoids and vitamins, in algae [6,7]. In addition, using in silico metabolic models to complement and contextualize genetic and metabolic data will provide researchers more options for the strain improvement of target products [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%